The willingness to pay for organic attributes in the UK - Adelina Gschwandtner; Michael P. Burton (University of Kent, School of Economics, 2017)
There has been almost no recent formal economic analysis of the WTP of British consumers for organic products. Given the rising demand for organic products on one hand and the decline in the organically farmed area in the UK on the other hand, this is an important topic to address. The present paper analyses the demand for organic products using both stated and revealed preferences from exactly the same consumers. The stated preference model is based on the respondent's choice from hypothetical choice sets. Attributes in the stated preference model are based on the ranges of the actual levels of attributes found in shops and are presented to respondents using a fractional factorial statistical design. Three different hypothetical bias treatments are applied in order to reduce hypothetical bias. The stated preference results are validated with the help of actual consumption data from the weekly shopping of the same consumers. The results show that there exists a core of organic consumers of about 20-30% of the sample that have a positive willingness to pay for the organic label. However, consumers seem to be willing to pay more for other attributes such as a higher quality, environmentally friendly production and no chemical usage. Attributes such as animal welfare, and a longer expiry date do not seem to have the same relevance for the UK consumers.
Keywords: 330